A novel motionless calibration method for augmented reality surgery navigation system based on optical tracker. Issue 12 (December 2022) - Wan, Xinjun; Shen, Lizhengyi; Fang, Zhiqiang; Dong, Shao; Zhang, Shilei; Lin, Chengzhong
Abstract: Augmented reality (AR) surgery navigation systems display the pre-operation planned virtual model at the accurate position in the real surgical scene to assist the operation. Accurate calibration of the mapping relationship between the virtual coordinate and the real world is the key to the virtual-real fusion effect. Former calibration methods require the doctor user to conduct complex manual procedures before usage. This paper introduces a novel motionless virtual-real calibration method. The method only requires to take a mixed reality image containing both virtual and real marker balls using the built-in forward camera of the AR glasses. The mapping relationship between the virtual and real spaces is calculated by using the camera coordinate system as a transformation medium. The composition and working process of the AR navigation system is introduced, and then the mathematical principle of the calibration is designed. The feasibility of the proposed calibration scheme is verified with a verification experiment, and the average registration accuracy of the scheme is around 5.80mm, which is of same level of formerly reported methods. The proposed method is convenient and rapid to implement, and the calibration accuracy is not dependent on the user experience. Further, it can potentially realize the real-time update of the registration transformation matrix, which can improve the AR fusion accuracy when the AR glasses moves. This motionless calibration method has great potential to be applied in future clinical navigation research. Abstract : Augmented reality; Optical tracker; Surgical navigation; Virtual and real calibration; PNP.